Meningkatkan Keaktifan dan Hasil Belajar Matematika Dengan Implementasi Media Geogebra Pada Siswa SMA - Surya Mayadi (Universitas Hamzanwadi, 2021)
This study aims to increase the activeness and mathematics learning outcomes of students through the implementation of Geogebra learning media. This type of research is the PTK (Classroom Action Research). The subjects receiving the action were class X MIPA 3 students of SMA Negeri 1 Selong in the 2019/2020 school year, totaling 36 students. The data collection method used is the method of documentation, observation and test methods. The data analysis technique used is the process of data analysis, data presentation, and data verification. The results showed an increase in student activeness and learning achievement in the Trigonometric Function Graph material. This can be seen from: 1) There was an increase in the average student learning activeness from 58.8 in the initial state to 63.4. In other words, there was an increase from medium criteria to high criteria. 2) There is an increase in the average student achievement from 67 in the initial state to 76 in the first cycle and to 81 in the second cycle. Likewise, the percentage of students who reached the KKM from 44.4% in the initial conditions, to 63.9% in the first cycle and an increase of 80.6% in the second cycle.